(untitled) (Proceedings of International Conference on Special Education, 2015)
Sensory integration (SI) is the brain’s ability to organize and process information received from the environment through different senses. SI is also the cognitive capacity to extract information from these senses and associate that information with prior memories, experiences, and knowledge already in the mind. Proper sensory integration means that we continually comprehend who we are, what we’re doing, and where we’re doing it. Sensory integration should develop naturally. Recent studies show that students with different types of Special Education Needs or under-average learning achievements may have underlying Sensory Integration Deficits or Sensory Processing Disorders (SPD). These students usually show problems in self-care, play repertoire, social engagement and academic performance. This presentation share the use Sensory Integration Therapy by registered occupational therapists In Hong Kong. The importance of collaborative efforts with school teachers, and families is also discussed.